Th1 polarization of the immune response in uveitis in Behçet's disease - Ilhan, Fulya; Demir, Tamer; Türkçüo?lu, Peykan; Turgut, Burak; Demir, Nesrin; Gödekmerdan, Ahmet (Elsevier B.V., 2008)
Background: It has been reported that abnormalities in the balance of T-helper cells type 1/2 (Tb1/Th2) may account for the pathophysiology of human autoimmune diseases. The purpose of this study was to define the role of the Th1/Th2 balance in the pathogenesis of uveitis in Behçet's disease (BD). Methods: From February 2003 to August 2005, we studied 31 patients with active BD. Of these patients, 21 (12 female, 9 male; mean age 35.5 [SD 10] years) presented with acute uveitis, and 10 (7 female, 3 male; mean age 34 [SD 11] years) presented with inflammatory arthritis but no prior uveitis attack. The control group consisted of 10 (7 female, 3 male; mean age 34.7 [SD 8] years) age-matched, healthy individuals. CD4+ CD26+ and CD4+ CD30+ cell surface expression of the peripheral blood CD4+ T lymphocytes was evaluated by analytic flow cytometry in order to determine percentages of Th1 and Th2 lymphocyte subsets. Results: The mean percentage of CD4+ CD26+ and CD4+ CD30+ cells was 26.27 (SD 6.18) % and 2.56 (SD 0.82) %, 17.42 (SD 5.90) % and 2.86 (SD 0.72) %, and 14.99 (SD 3.96) % and 3.11 (SD 1.25) % in BD with active uveitis, BD with inflammatory arthritis but no prior uveitis attack, and control groups, respectively. T-helper 1 (Th1) cell percentage was significantly higher in the BD with active uveitis group than the BD with arthritis and no prior uveitis attack group (p = 0.001). With respect to the percentage of CD30+ Th2 cells, there was no statistical difference between the 2 BD groups (p = 0.529) or among the 3 groups (p = 0.375). Interpretation: Th1 lymphocyte dominance in peripheral circulating blood may play a role in the pathogenesis of BD uveitis.
Keywords: Behçet's disease; Th1/Th2 balance; Uveitis